Ban on menthol-flavoured tobacco products predicts cigarette cessation at one year: a population cohort study - Chaiton, Michael (Tob Control, 2019)
OBJECTIVES: The province of Ontario, Canada, banned the use of menthol-flavoured tobacco products as of January 1(st), 2017. The long-term impact of a menthol ban on smoking behaviour has not been previously evaluated. METHODS: Population cohort study with baseline survey conducted September-December 2016 and follow up January-August 2018 among residents of Ontario, Canada, 16 years old and over who reported current smoking (past 30 days) at baseline survey and completed follow up (n=913) including 187 reporting smoking menthol cigarettes daily, 420 reported smoking menthol cigarettes occasionally, and 306 were non-menthol cigarette smokers. Relative rates of making a quit attempt and being a non-smoker at follow up were estimated with Poisson regression controlling for smoking and demographic characteristics at baseline. RESULTS: At follow up, 63% of daily menthol smokers reported making a quit attempt since the ban compared to 62% of occasional menthol smokers and 43% of non-menthol smokers (adjusted relative rate (ARR) for daily menthol smokers compared to non-menthol smokers: 1.25; 95% CI 1.03-1.50). At follow up, 24% of daily menthol smokers reported making a quit since the ban compared to 20% of occasional menthol smokers and 14% of non-menthol smokers (ARR for daily menthol smokers compared to non-menthol smokers: 1.62; 95% CI 1.08, 2.42). CONCLUSIONS: The study found a higher rates of quitting among daily and occasional menthol smokers in Ontario one year after the implementation of a menthol ban compared to non-menthol smokers.. Our findings suggest that restrictions on menthol may lead to substantial improvements in public health.